(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the economic essence of taxes, their role in the fiscal system, and their importance in forming state budget revenues. It also discusses types of taxes, their functions, their role in the state financial system, and their significance in ensuring economic stability. The study provides scientifically grounded conclusions on increasing budget revenues through taxation and improving the tax system.